Pathologic response evaluation of localized or locally advanced esophageal carcinoma to induction chemotherapy followed by preoperative concurrent chemotherapy and hypofractionated radiotherapy: a clinical trial - Emadi Torghabeh, Ali; Aledavood, Seyed Amir; Soltani, Ehsan; Akbari Oryani, Mahsa; Akhlaghi, Saeed; Hosseini, Sare; Fani Pakdel, Azar; Taghizadeh Kermani, Ali; Anvari, Kazem; Shahidsales, Soodabeh; Bahadorian, Shahrzad; Mashreghi Moghaddam, Shervin (Frontiers in Oncology, 2024)
Objective: Esophageal cancer is a therapeutic challenge in most healthcare systems. Most patients present with locally advanced disease at diagnosis. Concurrent chemoradiotherapy (CRT) is the standard treatment for locally advanced esophageal carcinoma. Since achieving a complete pathological response in postoperative specimens following neoadjuvant therapy is associated with improved patient survival, this study was designed to evaluate the pathologic response of localized or locally advanced esophageal carcinoma to induction chemotherapy followed by preoperative concurrent chemotherapy and hypofractionated radiotherapy (HFR).Methods: This single-arm clinical trial (IRCT20210623051676N1) evaluated patients with squamous cell carcinoma or adenocarcinoma of the esophagus, stage cT2-T4a N0 M0 or cT1-4a N+ M0. Patients received 3-5 cycles of weekly induction chemotherapy with the paclitaxel (50 mg/m2) and carboplatin (AUC=2) regimen, followed by weekly concurrent CRT with the same chemotherapy regimen. The radiation dose was 40 Gy, delivered over 16 fractions, 5 days per week (2.5 Gray/fraction). Patients underwent surgery 4-6 weeks after completion of CRT. The surgical specimens were evaluated for pathological response. A p-value of < 0.05 was considered significant in all analyses.Results: Out of 54 patients enrolled in this study, 45 completed the neoadjuvant protocol. Of these 45 patients, 32 underwent surgery and were finally analyzed. The mean age of the patients was 59.9 ± 8.6 years (range, 37-75 years). The location of the tumor was in the mid-thoracic esophagus in most patients (21, 65.6%) and the most common histological type was SCC (29, 90.6%). The median number of induction and concurrent chemotherapy cycles was 5 (4.8 ± 1.3 course, range, 1-10) and 3 (2.6 ± 0.8 course, range, 0-4), respectively. Among 45 patients who completed the neoadjuvant protocol, the most common toxicities were grade 3 neutropenia (15.6%), acute renal failure (4.4%), and odynophagia (37.8%). Nearly two-thirds of the patients experienced complete or near-complete responses (71.9%, 23 patients). Partial response was reported in 6 patients (18.8%) and poor response in 3 patients (9.4%).Preoperative induction chemotherapy followed by HFR with concurrent chemotherapy has low toxicity and side effects, good tolerance, and significant efficacy in the treatment of patients with esophageal cancer.